Mapping the past : from sampling sites and landscapes to exploring the 'archaeological continuum' : proceedings of the XVIII UISPP World Congress (4-8 June 2018, Paris, France). - Dabas, Michel,; Campana, Stefano,; Sarris, Apostolos, (Archaeopress Archaeology, 2020)
These papers reflect on the need to develop sustainable and reliable approaches to mapping our landscape heritage, guided by the crucial concept termed the 'archaeological continuum'.